FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Rinawati, Rinawati; Khresna Dewi, Vonny; Tunggal, Tri; Rafidah, Rafidah (Jurnal Keperawatan dan Kesehatan, 2026)
Background: According to the World Health Organization (WHO), pneumonia is the leading cause of death in children under five worldwide, the "forgotten child killer." The incidence of pneumonia at the Amuntai Selatan Community Health Center reached 80.59% cases in 2024. Pneumonia can be caused by nutritional status, immunization status, and exposure to cigarette smoke. Objective: To find out the factors associated with the incidence of pneumonia in toddlers at the South Amuntai Community Health Center. Methods: This study used an observational analytical design with a case-control approach. The sample was drawn using systematic sampling with a ratio of 141 cases to 282 controls. Data were analyzed using the Chi-Square tests and Odds Ratio. Results: A total of 141 toddlers (33.3%) experienced pneumonia. Fifty-one toddlers (12.1%) had poor nutritional status. A total of 144 toddlers (34.0%) had incomplete immunization status. Conclusion: There was a correlation between nutritional status (P=0.027), immunization status (P=0.000, OR=2.099), and cigarette smoke exposure (P=0.000, OR=2.134) and the incidence of pneumonia. Parents of toddlers should ensure balanced nutrition, provide their children with complete basic immunizations to ensure good immunity against various diseases, especially pneumonia, and avoid smoking near toddlers.